A study of bush encroachment in Hluhluwe National Park, using aerial photographs within a GIS framework - Aston, Tim (Department of Biological Sciences, 2023)
Bush encroachment has been an ongoing process since the proclamation of the Hluhluwe Reserve. In this paper, I assess both the total extent of bush encroachment over the last 40 years for a section of the reserve (9.1 %}, as well as which landscape factors pre-dispose areas to encroachment in that section. Aerial photographs from 1960 were linked together and aligned to an orthorectified Image from 2000, which had been georeferenced and aligned to the GIS database that exists for the area. Areas of closed canopy vegetation were converted into polygons, and the physical attributes of the areas that had been encroached Upon were extracted from the GIS database that exists for the area. Classification trees were used for the analysis of landscape correlates of encroachment. Fire frequency and the area of forest within 200m of a point in? 1960 were Identified as being the main factors determining which areas had been encroached upon